Citra Mubalig Kodam XIV/Hasanuddin di Media Sosial - saleh syahrir, muhammad; Muhammad Saleh Syahrir; Ramsiah Tasruddin; Rahmawati Haruna (Interaction: Jurnal Sosiologi Komunikasi, 2025)
This research examines Mubalig Kodam XIV / Hasanuddin's distinctive social media branding strategy for da'wah communication. The research methodology involves a qualitative approach, with data collected from interviews with five key informants and content analysis of lectures uploaded to social media on Facebook, Instagram, and TikTok in 2024 by the XIV Hasanuddin regional commander's preachers. The study unearthed three significant findings. Firstly, the innovative use of platform-specific strategies is pivotal in optimizing engagement. Facebook serves as a platform for in-depth religious discussions. On the other hand, Instagram emphasizes visual storytelling with series such as "Hadith in Uniform," and TikTok effectively targets younger audiences with short videos like "Rapid Fiqh." Secondly, audience engagement is bolstered through strategic posting times, direct interaction, and personalized responses. The peak engagement period is during the evening (6–8 PM local time). Live question-and-answer sessions significantly reduce the number of absent viewers compared to pre-recorded content. Thirdly, the preachers' image combines religious authority with military values, projecting credibility and moral integrity. This hybrid identity is reinforced through uploads that feature community service, avoid divisive political commentary, and maintain a balance between institutional and religious messages. Through these strategies, Mubalig Kodam XIV/Hasanuddin demonstrates how social media can be an effective tool for modern da'wah, leveraging its potential to reach diverse audiences while maintaining theological authenticity. The study offers practical recommendations, such as developing training modules for specific platforms, better content vetting processes, and an "algorithmic ijtihad" framework for adapting religious messages to digital platforms. These recommendations provide actionable insights for improving social media engagement in religious contexts.